Stylistic devices in English film titles containing the words “heart” and “soul” with reference to Vietnamese equivalents / Quach Thi Phuong; NHDKH Assoc.Prof.Dr Nguyen Thi Thanh Huong - Quach, Thi Phuong
The theoretical frameworks are stylistic devices, syntax and translation. This study mainly focuses on finding out lexical and syntactical stylistic devices in 117 English film titles, syntactical features of these titles and evaluation of some Vietnamese translations basing on determined stylistic devices and film plots. Various methods have been adopted but descriptive and analysis method is the main method because it is synthetic or analytic in its approach. First, the findings show that most English film titles are written in the form of phrases, mostly noun phrases because its condense but simple language makes it easier for audiences to memorize the titles. Secondly, if lexical stylistic devices are found in most films, especially metaphor, epithet, metonymy, syntactical stylistic devices are very rare.7 lexical stylistic devices (metaphor, epithet, metonymy, simile, hyperbole, cliché, idiom) and 3 syntactical stylistic devices(inversion, parallel construction, antithesis) are figured out. Thirdly, the thesis emphasizes that most Vietnamese translators base on determined stylistic devices and film plot when translating these English film titles into Vietnamese.This study contributes in teaching and learning stylistic devices and translating English film titles into Vietnamese through its implications.